Individual differences in level of wisdom are associated with brain activation during a moral decision‐making task. Issue 6 (1st May 2019) - Thomas, Michael L.; Martin, Averria S.; Eyler, Lisa; Lee, Ellen E.; Macagno, Eduardo; Devereaux, Mary; Chiong, Winston; Jeste, Dilip V.
Abstract: Introduction: Wisdom is reportedly associated with better health and quality of life. However, our knowledge of the neurobiology of wisdom is still in the early stages of development. We aimed to improve our understanding by correlating a psychometric measure of the trait with patterns of brain activation produced by a cognitive task theorized to be relevant to wisdom: moral decision‐making. In particular, we aimed to determine whether individual differences in wisdom interact with moral task complexity in relation to brain activation. Methods: Participants were 39 community‐dwelling men and women aged 27–76 years, who completed moral and nonmoral decision‐making tasks while undergoing functional magnetic resonance imaging. Brain activation in select regions of interest was correlated with participants' scores on the San Diego Wisdom Scale (SD‐WISE). Results: Individual differences in wisdom were found to interact with brain response to moral versus nonmoral and moral personal versus impersonal dilemmas, particularly in regions in or near the default mode network. Persons with higher scores on the SD‐WISE had less contrast between moral and nonmoral dilemmas and greater contrast between moral‐personal and moral‐impersonal dilemmas than individuals with lower SD‐WISE scores. Conclusions: Results confirmed our hypothesis that individual differences in level of wisdom would interact with moral condition in relation to brain activation, and may underscore the relevance of considering one's own and others' actions and experiences in the context of wise thinking. Future studies are needed to replicate these findings and to examine specific neurocircuits. Abstract : We aimed to improve our understanding of wisdom by correlating a psychometric measure of the trait with patterns of brain activation produced by a cognitive task theorized to be relevant to wisdom: moral decision‐making. Individual differences in wisdom were found to interact with brain response to moral versus nonmoral and moral personal versus impersonal dilemmas, particular in regions in or near the default mode network. Results may underscore the relevance of considering one's own and others' actions and experiences in the context of wise thinking.